Leadership in Action Agent of Change - A Talk with Marshall Goldsmith - Alexander, John (Center for Creative Leadership, 2000)
Successful people are always successful because of many things and in spite of some things, according to coach and consultant Marshall Goldsmith. Helping executives understand this and change ineffective behavior is Goldsmith's challenge.